Kedudukan Hukum Yayasan Panti Asuhan sebagai Wali Atas Anak-Anak Panti Asuhan - Muhammad Al Habsy Ahmad (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
The purpose of this study was to determine the validity of the orphanage foundation in acting as the guardian of the orphanage children. And to know the legal responsibility of the orphanage foundation as the guardian of the orphanage children. The research was conducted in the Mamuju City area with the consideration that the object of the problem discussed was located in Mamuju. The selection of this location is also due to the consideration that this location can provide the data that the author needs in discussing problems related to the writing of this thesis. This research uses a qualitative method which is then presented descriptively, namely by describing, describing, and explaining things that are in accordance with the problems that are closely related to this research. Orphanage foundations as guardians depend on the court's decision to appoint them as guardians. The appointment of the orphanage foundation as the guardian must be determined by the judge of the local Religious Court in accordance with the position of the orphanage foundation. Then the legal responsibility of the orphanage foundation as a guardian is the same as other guardians that have been regulated in the legislation, where each guardian must carry out the maintenance and education of the child's personality and manage his assets, and must represent him in carrying out legal actions. However, the provisions regarding this responsibility are not carried out by the orphanage foundation because the position of the orphanage foundation in carrying out childcare activities is only as a social institution that carries out its function as a social service institution for children who do not get good care in their family and the foundation is not as guardians of the children entrusted to the foundation. So to find out the responsibility of the foundation as a social institution can be seen in the provisions of the foundation law and the household articles of association of the foundation's establishment.